2014
DOI: 10.9745/ghsp-d-14-00043
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects of heat exposure and storage conditions of Oxytocin-in-Uniject in rural Ghana: implications for scale up

Abstract: Oxytocin-in-Uniject devices could be stored 30 to 40 days without refrigeration under typical field conditions, with wastage levels below 10%, based on simulation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…Limited data suggest that OT is resistant to freeze-thaw cycle in urines [21]. OT used as a drug was stable for 12 months at 4°C and for 1 month at 25°C [22]. However, these conditions do not reflect the conditions of our study.…”
Section: Discussionmentioning
confidence: 69%
“…Limited data suggest that OT is resistant to freeze-thaw cycle in urines [21]. OT used as a drug was stable for 12 months at 4°C and for 1 month at 25°C [22]. However, these conditions do not reflect the conditions of our study.…”
Section: Discussionmentioning
confidence: 69%
“…Vaccine vial monitors (VVM = TTI for vaccines) have been used for all WHO prequalified vaccines since 1996 and are included among the minimum requirements in all international tenders by all United Nations procurement agencies and any member states . A simulation study involving TTIs with oxytocin used VVM type 30 (meaning that VVM will reach its discard point in 30 days if kept at 37°C constant temperature), found that a considerable number of oxytocin samples were rejected although they were still within acceptable specifications . However, we must note that VVM is not a potency indicator and is designed to warn health workers on the impact of time and temperature on the product with a reasonable safety margin.…”
Section: Discussionmentioning
confidence: 99%
“…The Uniject single-use prefilled syringe, which does not require additional sterile equipment, eliminates the need for dosage estimation and can be used by unskilled personnel ( Diop et al, 2016 , Tsu et al, 2003 , Tsu et al, 2009 , Althabe et al, 2011 , Strand et al, 2005 , Stanton et al, 2013 ). However, the Uniject devices still require maintenance of cold-chain supply, and a study in rural Ghana highlighted that the single-use prefilled syringe was highly sensitive to small changes in ambient temperature and could expire in as few as 6 days ( Mullany et al, 2014 ). The preferred approach would be the development of a heat-stable, non-parenteral oxytocin formulation as identified by the UN Commission on Life-saving Commodities for Women and Children ( United Nations, 2012 ).…”
Section: Discussionmentioning
confidence: 99%